2003
DOI: 10.1093/annonc/mdg259
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood circulating cytokeratin-19 mRNA-positive cells after the completion of adjuvant chemotherapy in patients with operable breast cancer

Abstract: The detection of CK-19 mRNA-positive cells in the peripheral blood after adjuvant chemotherapy may be of clinical relevance for patients with early breast cancer and less than four involved axillary lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 28 publications
5
51
0
7
Order By: Relevance
“…Since chemotherapy cannot in many cases eliminate the disseminated [29] or/ and the circulating [30] tumor cells, it is important to target these occult tumor cells by using novel therapeutic approaches, such as monoclonal antibodies or other drugs acting on specific molecular targets. In a previous study, the administration of transtuzumab, a humanized anti-HER2 monoclonal antibody, resulted in a significant decrease of the HER2-positive CTCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Since chemotherapy cannot in many cases eliminate the disseminated [29] or/ and the circulating [30] tumor cells, it is important to target these occult tumor cells by using novel therapeutic approaches, such as monoclonal antibodies or other drugs acting on specific molecular targets. In a previous study, the administration of transtuzumab, a humanized anti-HER2 monoclonal antibody, resulted in a significant decrease of the HER2-positive CTCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chemoresistant CTCs or DTCs has been previously described (Braun et al, 2000a;Xenidis et al, 2003Xenidis et al, , 2009) and attributed to the low proliferative capacity of these cells (Pantel et al, 1993;Muller et al, 2005). Therefore, it could be hypothesised that the detection of occult tumour cells after the completion of adjuvant chemotherapy could be used as a surrogate marker for the efficacy of the adjuvant treatment used.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that the persistence of occult tumour cells in the bone marrow (Wiedswang et al, 2004;Janni et al, 2005) or peripheral blood (Xenidis et al, 2003(Xenidis et al, , 2009 after adjuvant chemotherapy or during follow-up is associated with an adverse clinical outcome. In this study, the detection of CTCs and/or DTCs after chemotherapy was not associated with increased risk for relapse or death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that investigated the prognostic value of CTCs/DTCs at the time of completion of adjuvant therapy [42, 106,107] showed that the detection of DTCs [42,108] and CTCs [106] after the completion of chemotherapy is associated with an unfavorable clinical outcome [103,105]; further reviewed by Ignatiadis et al [109]. In keeping with this work suggesting diagnostic and prognostic relevance for CK19, more recently full-length CK19 has been detected in bone marrow specimens from breast cancer patients and is associated with the presence of overt metastases and poor survival rates [110].…”
Section: Cytokeratin 19mentioning
confidence: 99%